Antibacterial and anti-biofilm activity, and mechanism of action of pleurocidin against drug resistant Staphylococcus aureus. (February 2019) - Ko, Su Jin; Kang, Na Hee; Kim, Min Kyung; Park, Jonggwan; Park, Eunji; Park, Ga Hyeon; Kang, Tae Woo; Na, Da Eun; Park, Jin Bae; Yi, Yae Eun; Jeon, Seung Hun; Park, Yoonkyung
Abstract: The abuse of antibiotics has resulted in the emergence of multi-drug-resistant bacteria. Staphylococcus aureus is a frequent cause of infections, and antibiotic-resistant S. aureus has become a serious problem. Antimicrobial peptides play an important role in innate immunity and are attracting increasing attention as alternative antibiotics. In a previous study, pleurocidin, derived from winter flounder, was identified as a 25-amino acid antimicrobial peptide with no cytotoxicity toward mammalian cells and low hemolytic activity. In the present study, pleurocidin was observed to exhibit antimicrobial activity against gram-positive and gram-negative bacteria, especially against drug resistant S. aureus . Pleurocidin retained its antibacterial activity against drug resistant S. aureus in the presence of a physiological salt concentration. Membrane depolarization assays and propidium iodide uptake indicated that pleurocidin kills bacteria by damaging the integrity of the bacterial membrane. DNA binding assays revealed that pleurocidin binds to DNA. Thus, pleurocidin targets not only the bacterial membrane, but also their DNA. S. aureus biofilms have become a serious problem because of increased resistance to antibiotics. Therefore, we investigated the effect of pleurocidin on biofilm inhibition and eradication using crystal violet staining and microscopic observation. Pleurocidin inhibited and eradicated biofilms at low concentrations. Taken together, the results suggested that pleurocidin is a promising candidate therapeutic agent to treat drug-resistant bacteria and biofilm-related infections. Highlights: Pleurocidin kill the bacteria, especially drug resistant S. aureus and no cytotoxicity. Pleurocidin have ability to inhibit and remove S. aureus biofilm formation. Pleurocidin maintains its antibacterial activity in physiological salt concentration. Pleurocidin can be developed a drug candidate against drug resistant bacteriaights